Writing and society an introduction - Coulmas, Florian (Cambridge Cambridge University Press, 2013)
"How does writing relate to speech? What impact does it have on social organisation and development? How do unwritten languages differ from those that have a written form and tradition? This book is a general account of the place of writing in society. Drawing on contemporary and historical examples, from clay tablets to touchscreen displays, the book explores the functions of writing and written language, analysing its consequences for language, society, economy and politics. It examines the social causes of illiteracy, demonstrating that institutions of central importance to modern society are built upon writing and written texts, and are characterised by specific forms of communication. It explores the social dimensions of spelling and writing reform, as well as of digital literacy, a new mode of expression and communication posing novel challenges to the student of language in society"-- Provided by publisher.
Machine generated contents note: 1. The tyranny of writing; 2. The past in the present and the seeds of the public sphere; 3. Written and unwritten language; 4. Literacy and inequality; 5. The society of letters; 6. Writing reform; 7. Writing and literacy in the digitalized world.
Includes bibliographical references (p. 155-170) and index.
Keywords: Writing -- Social aspects; Written communication -- Social aspects; Literacy -- Social aspects